The Role of Nurses in Improving the Quality of Life of Neonates Through Pain Management: A Literature Review - Dessirya, Endah; Widhiastuti, Erma (GLOBAL HEALTH SCIENCE GROUP, 2024)
Pain in neonates is a problem that must be taken seriously. In addition to causing physiological disturbances, pain in neonates can have long-term consequences including behavioural changes, hypersensitivity to pain and neurodevelopmental disorders. Nurses have an important role in improving the quality of life of neonates through pain management. This study aims to provide alternatives in the prevention of pain in neonates non-pharmacologically and is expected to apply pain instruments (as a basis for pain assessment) and improve collaboration, education and supervision in the prevention of pain in neonates. The method used in this study was literature review. Searching academic articles through Online Database searches through ClinicalKey for Nursing, Proquest, Science Direct and Pubmed from 2020-2024 with the Prisma approach, then filtering with PICO (Population, Intervention, Comparative, Outcome) obtained 10 suitable articles. Based on several studies, the role of nurses in improving the quality of life of neonates is effective pain management through pain assessment, non-pharmacological interventions (skin to skin contact, breastfeeding, maternal voice, facilitated tucking positioning, massage, olfactive stimulation, sucrose administration, nesting positioning and Yakson touch therapy). In addition, education, supervision and a comprehensive approach and collaboration between teams are needed. Pain management in neonates is important in neonate care, it is recommended that there is a bundle of pain management in neonates which contains a structured plan, and integrated guidelines to prevent and manage pain in neonates.